Pengaruh Gaya Kepemimpinan Kepala Sekolah Terhadap Kinerja Guru di MTS Hidayatul Athfal Rebile Lombok Tengah - Baiq Nurul Hijjah; Jamiluddin (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, dan Publikasi, 2025)
The purpose of this study was to determine the effect of the principal's leadership style on teacher performance at MTs Hidayatul Athfal Rebile, Pujut District, Central Lombok Regency. This study used a quantitative method with the Spearman Rank correlation analysis technique. The results of the analysis showed a significant value of 0.177> 0.05, so H0 was accepted and Ha was rejected. This means that there is no significant relationship or influence between the principal's leadership style and teacher performance. The level of strength of the relationship between variables X (leadership style) and Y (teacher performance) based on the correlation coefficient value of 0.368, which is between 0.20–0.399, so it is interpreted as a low relationship according to the guidelines for interpreting the correlation coefficient. From the calculation of the coefficient of determination (R²), the influence of the principal's leadership style on teacher performance is 13.5%, while 86.5% is influenced by other factors. Based on these results, it can be concluded that the principal's leadership style has a low influence on teacher performance at MTs Hidayatul Athfal Rebile.